Wtręty rosyjskojęzyczne w relacjach polskich korespondentów zagranicznych - Pstyga, Alicja (Przegląd Rusycystyczny, 2017)
RUSSIAN INCLUSIONS IN THE REPORTS OF POLISH FOREIGN CORRESPONDENTS S u m m a r y This paper deals with one of the aspects of contemporary media communication: the work of the correspondents whose task is to present, interpret and evaluate events in the foreign country. The author of this article raises a question of Russian reality described to the Polish reader. The linguistic devices, especially Russian inclusions, employed in such texts should be thoroughly investigated. The problems which need special attention include decoding, double coding of information, expressing thoughts in another language as well as describing and interpreting the foreign reality. These phenomena are identified and analyzed in the reports written by Wacław Radziwinowicz, a foreign correspondent of the Polish newspaper Gazeta Wyborcza in Moscow until December 2015.